Application of chromosome microarray analysis and karyotyping in fetal cardiac abnormalities - Yun Guo; Xiaoqin Xin; Linju Zhou; Jungao Huang (Frontiers in Genetics)
ObjectiveChromosome microarray analysis (CMA) and karyotyping are two important genetic testing techniques used in prenatal diagnosis. This study aims to evaluate the value of chromosome microarray analysis and karyotyping in the diagnosis of fetal cardiac abnormalities, with particular focus on the detection of genomic copy number variations (CNVs).MethodsA retrospective analysis was conducted on 98 pregnant women diagnosed with fetal cardiac abnormalities through ultrasound between January 2022 and June 2024. Amniotic fluid samples from all participants were subjected to the analysis of karyotyping and Chromosome microarray analysis. The detection rates of both techniques in different types of fetal cardiac abnormalities were compared, and the outcomes of positive cases were followed up.ResultsOf the 98 fetuses with cardiac abnormalities, 12 cases showed abnormal genetic results, with a detection rate of 12.24%. Karyotyping identified 5 cases of abnormalities (5.10%), while the chromosome microarray analysis detected 11 cases (11.22%). In the group with isolated cardiac abnormalities (76 cases) and the group with cardiac abnormalities combined with other ultrasound abnormalities (22 cases), karyotyping detected 3.95% (3/76) and 9.09% (2/22) of abnormalities, with no significant statistical difference (P > 0.05). Chromosome microarray analysis detected abnormalities in 6.58% (5/76) of the isolated cardiac abnormalities group and 27.27% (6/22) in the group with combined abnormalities, showing a significant statistical difference (P < 0.05). Of the 12 positive cases, four were live births, eight were terminations, and postpartum cardiac abnormalities were found in two live births during follow-up.ConclusionChromosome microarray analysis has a higher detection rate in fetuses with cardiac abnormalities than traditional chromosome karyotyping, especially when fetal cardiac abnormalities are combined with other ultrasound abnormalities. It is recommended for clinical use to improve the detection of genetic alterations.